An Analysis of Supports for Persistence for the Military Student Population - Mentzer, Bruce D; Black, Ellen Lowrie; Spohn, R. Terry (Online Learning, 2014)
This study sought to describe the correlation of academic, financial, and social supports to the persistence of a military student population: veterans, active duty, and their families. The study also contrasted these relationships with non-military students and looked at the results of the overall group to persistence. Results confirmed the emphasis in the persistence literature on the importance of academic support mechanisms and noted its positive relationship to the military student population. Financial supports varied for the military student population, nonmilitary population, and the overall group with the military student population negatively impacted by loans, nonmilitary by university scholarships, and the overall group by government grants and aid. As an additional finding for this study, institutional support emerged as a key support mechanism. This study recommends enhancing academic and institutional support for the military student population to reinforce their persistence.